LEADERSHIP STRATEGY DURING TRANSITION PERIOD IN OPTIMIZING DEVELOPMENT PROGRAMS (A STUDY OF ACTING REGENTS IN LANGKAT REGENCY IN 2024-2025) - Ritonga, Putra Ansari; Bengkel, Bengkel; Irmayani, Tengku (Pena Cendekia Insani, 2025)
This study aims to examine the leadership strategies of regional heads during the transition period in optimizing development programs in Langkat Regency, North Sumatra Province. The research focuses on how the Acting Regent designs, implements, and optimizes strategies through special programs during the transition period. This research uses a qualitative approach with a case study method, and data collection techniques include in-depth interviews, literature review, and documentation. The results indicate that regional heads play a strategic role in initiating the Bubur Pedas (Bupati Collaborates to Pursue Regional Development Until Completed) program, a form of adaptive, collaborative, and innovative leadership. This program is able to build synergy between stakeholders and the community. However, obstacles such as limited fiscal resources, short terms in office, and negative public stereotypes pose challenges. This study confirms that the success of optimizing development programs is greatly influenced by the capacity and leadership style of regional heads during the transition period.